THE ASSERTIVE ACTS IN SPIDER-MAN NO WAY HOME MOVIE - Zega, Fatizatulo; Ambalegin, Ambalegin; Arianto, Tomi (IdeBahasa, 2024)
This qualitative research aimed at finding out the assertive acts. To fulfill the objective of this research, the researchers used Searle and Vanderveken’s theory about assertive acts. The theory was applied to the “Spider-man No Way Home” movie as the data source. The movie was chosen because the characters mostly uttered the truth about the hero’s struggles in the movie. In collecting the data, the researchers applied the observational method. This method was used to observe the use of language based on the context of an utterance and it was followed by a note-taking technique to get valid data. In analyzing the data, the researchers used the pragmatic identity method followed by the pragmatic competence in equalizing technique. This technique aimed to equalize the data with the theory pragmatically. Finally, the result was displayed narratively and descriptively. The researchers discovered twenty-three out of thirty-two acts of assertiveness. The acts were asserting, affirming, stating, denying, assuring, arguing, informing, reminding, objecting, predicting, reporting, suggesting, insisting, hypothesizing, guessing, swearing, admitting, confessing, accusing, blaming, praising, complaining, and boasting. The researchers did not find any claiming, disclaiming, rebutting, notifying, retrodicting, conjecturing, testifying, criticizing, or lamenting. The most frequently appeared was informing act. Characters' utterances contained more social meaning in conveying information to the interlocutors. The utterances were not only uttered by the speakers, who were the ones who got the effect, but also by the hearers. The utterances occurred because it was based on a situation that caused the speaker to express the statements